The Influence of Ease of Use, Hedonic Value, and Utilitarian Value on Purchase Intention in Social Commerce - Asih Kurnianingsih; Hendy Tannady; Rhian Indradewa; Regina Deka Sofia (Amal Insani Foundation, 2026)
The rapid development of social commerce has transformed online shopping from merely a functional transaction into an immersive social experience. This study aims to examine the influence of ease of use on purchase intention through a dual-path mechanism involving hedonic value and utilitarian value. Using a quantitative explanatory approach, data were collected through an online questionnaire distributed to 150 social commerce users in Indonesia, selected using purposive sampling techniques. Data analysis was conducted using Structural Equation Modelling-Partial Least Squares (SEM-PLS) with SmartPLS 4.0. The results indicate that four hypotheses were accepted while one hypothesis was rejected. Ease of use was found to have a positive and significant effect on hedonic value and purchase intention, but no significant effect on utilitarian value. Meanwhile, both hedonic value and utilitarian value positively and significantly influenced purchase intention. Furthermore, the indirect effect test confirmed the strong mediating role of hedonic value in the relationship between ease of use and purchase intention. These findings highlight that technological convenience serves as a key driver that should be transformed into emotional satisfaction and functional benefits to convert user visits into transactions. Therefore, platform developers are encouraged to synchronise navigation simplicity with interactive features to create a shopping ecosystem that is both enjoyable and efficient.